Efficacy and safety of peripherally-restricted κ-opioid receptor agonist-HSK21542 for postoperative analgesia in patients undergoing laparoscopic abdominal surgery: a randomized, placebo-controlled phase 2 trial - Yinbo Zhong; Haiying Wang; Min Yan; Mengchang Yang; Jiaqiang Zhang; Ling Nan; Zhiping Wang; Jianjun Yang; Jinglei Wu; Qulian Guo; Xiaoling Hu; Hongmeng Xu; et al. (Frontiers in Medicine)
BackgroundThis phase 2 trial comprised dose exploration (stage 1) and dose confirmation stages (stage 2) to determine the safety and efficacy of HSK21542 in patients undergoing laparoscopic abdominal surgery.MethodsIn stage 1, patients were randomly allocated at a ratio of 4:1 (12 to receive HSK21542, 3 to receive placebo) to 4 ascending dose groups in a sequential manner (group 1: preoperative HSK21542-0.4 μg/kg (or placebo) + HSK21542-0.2 μg/kg (or placebo) at postoperative 0 h, 8 h and 16 h; group 2: preoperative HSK21542-1.0 μg/kg (or placebo) + HSK21542-0.5 μg/kg (or placebo) at postoperative 0 h, 8 h and 16 h; groups 3 and 4: HSK21542-0.5 μg/kg or HSK21542-1.0 μg/kg (or placebo) at postoperative 0 h, 8 h and 16 h). In stage 2, patients received HSK21542-0.5 μg/kg, HSK21542-1.0 μg/kg or placebo postoperatively at 0 h, 8 h and 16 h in a 1:1:1 ratio. The primary endpoints in stage 1 were the safety outcomes including the incidence and severity of treatment-emergent adverse events (TEAEs) while the primary endpoint of stage 2 was the time-weighted summed pain intensity differences over 24 h (SPID0–24h).ResultsStage 1 enrolled 63 patients and 57 completed the trial, while 61 patients were enrolled in stage 2, and 60 completed the trial. The most common TEAEs were fever (22.9% vs. 41.7%), nausea (25.0% vs. 33.3%) and vomiting (22.9% vs. 25.0%) in the HSK21542 and placebo groups in stage 1. HSK21542 doses of 0.5 μg/kg and 1.0 μg/kg administered postoperatively were recommended for the subsequent stage 2. The pooled results revealed a slightly lower SPID0–24h in HSK21542-1.0 μg/kg group (−1,679.8 ± 2,284.3 scores × min) than those in HSK21542-0.5 μg/kg (−1,499.4 ± 2,487.2 scores × min) and placebo groups (−435.2 ± 2,852.9 scores × min; P = 0.114). A significantly higher least squares mean difference of pain intensity differences (PID) was found in HSK21542-1.0 μg/kg group compared to the placebo (P = 0.020).ConclusionHSK21542 at all dose regimens demonstrated well tolerability and safety comparable to that of the placebo among patients undergoing laparoscopic abdominal surgery in the phase 2 trial. The dosing regimen of HSK21542-1.0 μg/kg administered postoperatively at 0 h, 8 h and 16 h exhibited an acceptable efficacy, warranting its recommendation for further phase 3 trial.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT04424251.